Great estimations - Goldstone, Bruce (New York : Square Fish, 2010)
Photographs and easy-to-follow text teach children about estimations and offer tips to help them create accurate estimates.
Wilson's Children, October 2007
School Library Journal, November 2006
Booklist, September 2006
New York Times, November 2006
Horn Book, April 2007
Kirkus Review, September 2006
Keywords: Estimation theory -- Juvenile literature; Estimation theory; Approximate computation